Wi-Fi-Enabled Head Motion-Controlled Wheelchair for Quadriplegic Mobility - Dr Velayudham A,; Kamesh R,; Duraisaravanakkumar G,; Gowtham R A,; Kathikeyan S, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Quadriplegia is the condition that leads to a person's paralysis of all four limbs and the torso. In this case, the person completely or partially loses the ability to carry out activities and this affects the individual's autonomy. Although people with quadriplegia have greater difficulties to lead a normal life than those without, they often find means to integrate themselves into society. The traditional wheelchair (either manual or powered) needs either the physical strength or the hand-operated controls, which are difficult or impossible to use for individuals with limited or no upper body function. In order to break through the barriers, a Head Motion Controlled Wheelchair makes use of a cutting-edge solution. Through the discovery of head tilting transmitters for mobility purposes, users are able to move without the need of hand controls. With built-in motion detectors, microcontroller Unit, transmitters and receivers the device guarantees the operation is steady, and last but not least, it uses wireless communication. Safety functions such as fall detection mechanism and using a mobile app for emergency alerts step up the comfort of using it, and it is useful for people with quadriplegia.
Keywords: Head Motion detectors; Quadriplegics; MCUs; Transmitters and Receivers; GPS